The Impact of Implementing the Policy on the Formation and Structure of Regional Devices Based on Makassar City Regional Regulation No. 8 of 2023 on the Quality of Health Services in Makassar City (Case Study at the Makassar City General Hospital) - Rahmat, Laode Awal; Satispi, Evi; Dewi, Maya Puspita (International Journal of Social Service and Research, 2026)
This research examines the implementation of Makassar City Regional Regulation Number 8 of 2023 concerning the Formation and Composition of Regional Apparatus, a policy intended to strengthen institutional capacity and improve the quality of public health services. Using George C. Edwards III’s policy implementation framework, the research analyzes the influence of communication, resources, implementer attitudes, and bureaucratic structure on health service quality. The study applies a quantitative approach with descriptive and verification methods. Data were collected from 95 respondents consisting of Makassar City Hospital employees (doctors, nurses, and staff) and service users (patients). Primary data were obtained through questionnaires, supported by secondary data from desk research. Statistical analysis was conducted using path analysis techniques. The findings show that, partially, communication, resources, and implementer attitudes have a positive and significant effect on the quality of health services. In contrast, the bureaucratic structure does not have a significant partial effect. However, when analyzed simultaneously, all four factors—communication, resources, implementer attitudes, and bureaucratic structure—have a positive and significant influence on health service quality. The study concludes that effective policy implementation depends not only on formal organizational structures but also on how policies are communicated, supported by adequate resources, and implemented through positive attitudes of implementers. It recommends that the Makassar City Government and implementing agencies, particularly Makassar City Hospital, strengthen these aspects to enhance the success of current and future policy implementation and to continuously improve the quality of public health services.